Serum Dickkopf-1 signaling and calcium deposition in aortic valve are significantly related to the presence of concomitant coronary atherosclerosis in patients with symptomatic calcified aortic stenosis - Motovska, Zuzana; Vichova, Teodora; Doktorova, Magdalena; Labos, Marek; Maly, Marek; Widimsky, Petr (Journal of translational medicine, 2015)
BACKGROUND: The study aimed to assess serum RANKL:OPG ratio, Dkk-1 and deposition of calcium in aortic valve in relation to the presence of concomitant coronary atherosclerosis in patients with symptomatic calcified aortic stenosis (CAS). METHODS: OPG, soluble RANKL and Dkk-1 were measured in 218 consecutive patients who were undergoing cardiac catheterization because of symptomatic CAS. Values of studied compounds were compared between patients without (Group A) and with (Group B) coronary atherosclerosis. Computed tomography derived Agatston score was assessed by using 256-slice CT. RESULTS: Presence of coronary atherosclerosis was related to significantly (p = 0.007) higher OPG and to significantly (p = 0.004) lower Dkk-1. Coronary atherosclerosis was also associated with a trend towards a decrease of RANKL. RANKL/OPG Ratios (mean (95% C.I.)) were: 20.04 (16.58; 24.23) in Group A and 12.69 (9.96; 16.17) in Group B, resp., p = 0.018). After adjustment, the difference in RANKL:OPG ratios was no longer significant. Multivariable regression underscored the significance of difference in Dkk-1 (pafter adjustement = 0.020). Group A patients had significantly higher Dkk-1, significantly higher deposition of calcium in aortic valve and were symptomatic in significantly younger age (p < 0.001) as compared to group B patients: Agatston score (mean (95% C.I.)) 4069.9 (3211.8; 5134.5) and 2413.5 (1821.3; 3198.1), p = 0.007. CONCLUSIONS: Dkk-1 and deposition of calcium in aortic valve differ significantly in relation to the presence/absence of coronary atherosclerosis in patients with symptomatic CAS. A positive association was found between Dkk-1 and calcium load in aortic valve in patients with symptomatic CAS and angiographically normal coronary arteries.
Keywords: Coronary Artery Disease; nemoci koronárních tepen; počítačová rentgenová tomografie; Calcium; signální transdukce; Signal Transduction; aortální stenóza; Humans; Calcinosis; vývoj kostí; vápník; Aged; Female; Models, Biological; kalcinóza; senioři; lidé; Aortic Valve Stenosis; Intercellular Signaling Peptides and Proteins; Bone Development; ženské pohlaví; mezibuněčné signální peptidy a proteiny; Male; Tomography, X-Ray Computed; biologické modely; mužské pohlaví; aortální chlopeň; Aortic Valve